PPR14 Interacts With PPR-SMR1 and CRM Protein Zm-mCSF1 to Facilitate Mitochondrial Intron Splicing in Maize - Wang, Hong-Chun; Chen, Zongliang; Yang, Yan-Zhuo; Sun, Feng; Ding, Shuo; Li, Xiu-Lan; Xu, Chunhui; Tan, Bao-Cai (Frontiers in Plant Science, 2020)
In plants, splicing of organellar group II introns involves numerous nucleus-encoded trans-factors. But, how these trans-factors function and interact is not well understood. Here we report the function of a pentatricopeptide repeat (PPR) protein PPR14 and its physical relationship with other splicing factors in mitochondria. Null mutations of PPR14 severely arrest the embryo and endosperm development, causing an empty pericarp phenotype. PPR14 is required for the splicing of NADH dehydrogenase 2 (nad2) intron 3 and nad7 introns 1 and 2 in mitochondria. The absence of nad2 and nad7 transcripts leads to disruption of the mitochondrial complex I assembly and abolishes its NADH dehydrogenase activity. This is accompanied with increased levels of other mitochondrial complexes and elevated expression of the alternative oxidase proteins. As the function of PPR14 overlaps with PPR-SMR1 and the CRM-domain containing protein Zm-mCSF1, we tested their interactions. Protein-protein interaction analysis indicated that PPR14 interacts with PPR-SMR1 and Zm-mCSF1, suggesting that these three proteins may form a complex. As PPR proteins and CRM-domain containing proteins have many members in mitochondria and chloroplasts, we propose that organellar group II intron splicing is probably mediated by a dynamic complex that includes different PPR and CRM proteins in plants.